Analisis SWOT Potensi BUMDes Mitra Sejahtera Desa Sikapat - Raden Rifqi Dwi Santo; Joval Ifghaniyafi Farras (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
This article discusses the strategy for developing Mitra Sejahtera Village-Owned Enterprises (BUMDes) in Panggang Village with a focus on empowering Micro, Small and Medium Enterprises (MSMEs). Suhuat Village, although rich in natural potential, faces a number of challenges in optimizing its potential. Through the application of SWOT Analysis, this research investigates the internal strengths, operational weaknesses of BUMDes, as well as external opportunities and threats amidst the social and economic dynamics of Suhuat Village. The aim is to provide an in-depth understanding of the condition of BUMDes Mitra Sejahtera, to identify effective strategies for exploiting local potential, overcoming internal obstacles and facing external challenges. Research methods involve literature studies, interviews, document analysis, surveys, and field observations. The results of the SWOT analysis highlight the success of BUMDes in managing natural potential, MSMEs, and collaboration with external parties. The conclusion emphasizes the importance of management training, development of facilities and infrastructure, as well as closer collaboration with the government and related parties. This article is a reference for policy makers and researchers who are interested in empowering the local economy through BUMDes, which can contribute to sustainable development at the village level.